2015
DOI: 10.1111/imm.12465
|View full text |Cite
|
Sign up to set email alerts
|

Distinct sustained structural and functional effects of interleukin‐33 and interleukin‐25 on the airways in a murine asthma surrogate

Abstract: SummaryInterleukin-25 (IL-25) and IL-33, which belong to distinct cytokine families, induce and promote T helper type 2 airway inflammation. Both cytokines probably play a role in asthma, but there is a lack of direct evidence to clarify distinctions between their functions and how they might contribute to distinct 'endotypes' of disease. To address this, we made a direct comparison of the effects of IL-25 and IL-33 on airway inflammation and physiology in our established murine asthma surrogate, which involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Previous studies have strongly implicated IL‐33 in playing a key role in the pathogenesis of the airways mucosal inflammation that typically accompanies human asthma . In our own previous studies we showed that direct, per‐nasal application of IL‐33 alone to the murine airway is sufficient to cause asthma‐like inflammation, including subepithelial deposition of collagens .…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Previous studies have strongly implicated IL‐33 in playing a key role in the pathogenesis of the airways mucosal inflammation that typically accompanies human asthma . In our own previous studies we showed that direct, per‐nasal application of IL‐33 alone to the murine airway is sufficient to cause asthma‐like inflammation, including subepithelial deposition of collagens .…”
Section: Discussionmentioning
confidence: 67%
“…It is worth noting again, however, that IL‐33 challenge alone did not precisely recapitulate the effects of OVA sensitization and challenge because, for example, under the particular conditions of our experiments it did not result in elevation of MMP2 expression. Although we cannot discern the precise explanation for this, we speculate that one possible explanation is that, being a murine surrogate of ‘allergic asthma’, the airways inflammation induced in the OVA sensitization/challenge model is IgE‐dependent, whereas we previously detected no role for IgE in the airways inflammation induced by direct IL‐33 challenge . In this regard, it is interesting that deletion of the St2 gene partially but significantly reduced OVA‐induced MMP2 expression, suggesting that the IL‐33/ST2 axis does contribute, at least partially and indirectly, to the production of MMP2 in asthma.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations